2022
DOI: 10.1111/cns.13849
|View full text |Cite
|
Sign up to set email alerts
|

Acute high‐altitude hypoxia exposure causes neurological deficits via formaldehyde accumulation

Abstract: Acute high-altitude hypoxia exposure causes multiple adverse neurological consequences, including paralysis, blindness, sleep disturbance, mental disorder, and cognitive impairment. 1 Intellectual abilities such as concentration, perception, executive function, learning, and memory can be impaired, 2 which are caused by neuronal damage due to oxidative stress, inflammation, and other mechanisms. 3 However, the exact cellular and molecular mechanism of neurological dysfunction remains unclear. Therefore, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 59 publications
(104 reference statements)
1
12
0
Order By: Relevance
“…Studies have shown that HA exposure elicits remarkable alterations in iron metabolism, leading to disturbances in iron homeostasis and giving rise to toxicities such as inflammation, oxidative stress, and ferroptosis [ 7 , 8 , 9 , 10 , 12 ]. Yet, as far as we know, no relevant study has examined these effects on adipose tissue during HA treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have shown that HA exposure elicits remarkable alterations in iron metabolism, leading to disturbances in iron homeostasis and giving rise to toxicities such as inflammation, oxidative stress, and ferroptosis [ 7 , 8 , 9 , 10 , 12 ]. Yet, as far as we know, no relevant study has examined these effects on adipose tissue during HA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis is a novel kind of self-regulated cell death characterized by excessive iron-dependent oxidative stress and lipid peroxidation [ 22 , 23 ]. Acute exposure to HA may induce neuronal iron elevation and ferroptosis, subsequently leading to neurological deficits [ 12 ]. We investigated alterations in the ferroptosis signaling pathway in the adipose tissue of HA mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As an environment featuring hypobaric hypoxia, high altitude (HA) exposure increased ferroptosis sensitivity in adipose tissue with elevated levels of iron, ROS, MDA, and 4-HNE, as well as GSH depletion [ 134 ]. Acute high-altitude hypoxia exposure in mice leads to cerebral formaldehyde accumulation to induce neuronal ferroptosis [ 135 ]. A recent study suggested that hypobaric hypoxia at high-altitude induces both apoptosis and ferroptosis via the JNK signaling pathway by depleting keratin 18 (Krt18) and elevating JNK3 (MAPK10), as well as increasing ASCL4 for ferroptosis [ 136 ].…”
Section: The Mechanism and Regulation Of Ferroptosis Modulated By Hyp...mentioning
confidence: 99%